The Influence of Tax Understanding, Education, Service Quality, and Tax Sanctions on the Compliance of Land and Building Tax (PBB-P2) Taxpayers in Cirebon Regency - Komala, Safitri Ratna; Indriyani, Rinni; Sari, Fitriya (CV. Tripe Konsultan, 2025)
This study analyzed the influence of tax understanding, education, service quality, and tax sanctions on taxpayer compliance in paying Rural and Urban Land and Building Tax (PBB-P2) in Cirebon Regency. A quantitative approach was used via a survey of 100 taxpayers. Data were processed through validity and reliability tests, classical assumption tests, and multiple linear regression. The results show that all four variables have a positive and significant effect on compliance, both partially and simultaneously. The final model records R = 0.890, R² = 0.792, Adjusted R² = 0.784, indicating that the four predictors explain 78.4% of the variance in compliance. The Education variable—operationalized as formal education level and participation in tax-related literacy/outreach—has a significant partial effect comparable in magnitude to service quality. These findings suggest that strengthening taxpayer literacy programs, improving service quality, and applying fair sanctions can meaningfully raise PBB-P2 compliance.